Splanchnic and Systemic Haemodynamic Derangement in Decompensated Cirrhosis - Søren Møller; Flemming Bendtsen; Jens H Henriksen (Canadian Journal of Gastroenterology)
Patients with cirrhosis and portal hypertension exhibit characteristic hemodynamic changes with hyperkinetic systemic circulation, abnormal distribution of blood volume and neurohumoral dysregulation. Their plasma and noncentral blood volumes are increased. Splanchnic vasodilation is of pathogenic significance to the low systemic vascular resistance and abnormal volume distribution of blood, which are important elements in the development of the concomitant cardiac dysfunction, recently termed 'cirrhotic cardiomyopathy'. Systolic and diastolic functions are impaired with direct relation to the degree of liver dysfunction. Significant pathophysiological mechanisms are reduced beta-adrenergic receptor signal transduction, defective cardiac excitation-contraction coupling and conductance abnormalities. Vasodilators such as nitric oxide and calcitonin gene-related peptide are among the candidates in vasodilation and increased arterial compliance. Reflex-induced, enhanced sympathetic nervous system activity, activation of the renin-angiotensin aldosterone system, and elevated circulation vasopressin and endothelin-1 are implicated in hemodynamic counter-regulation in cirrhosis. Recent research has focused on the assertion that the hemodynamic and neurohumoral abnormalities in cirrhosis are part of a general cardiovascular dysfunction, influencing the course of the disease with the reduction of organ function, with sodium and water retention as the outcome. These aspects are relevant to therapy.